Factors related to work accidents in welding workshops in Paleteang District, Pinrang Regency in 2025 - Harum, Habil; Abdillah, Abdillah; Jumadi, Handani; Pratiwi, Siska Wijayanti; Vonny.P, Vonny.P (Journal of Midwifery and Nursing, 2025)
Workplace accidents remain a major occupational health problem in Indonesia, particularly in the informal sector. According to the ILO, more than 2.78 million workers die each year due to accidents and occupational diseases. This study aims to analyze factors associated with workplace accidents among welding workshop workers in Paleteang District, Pinrang Regency, in 2025. This research employed a quantitative analytical method with a cross-sectional design and total sampling technique, involving 37 workers from 17 welding workshops. Data were analyzed using the Chi-Square test and Fisher’s Exact Test. The results showed no significant relationship between age or occupational safety and health (OSH) training and work accidents (p>0.05). However, there was a significant relationship between the use of personal protective equipment (PPE) and the incidence of work accidents (p=0.01). This study contributes scientifically by highlighting the critical role of consistent PPE use in improving occupational safety practices in the informal sector, particularly among small-scale welding workshops. It is recommended that workers consistently use complete PPE and that workshop owners enhance OSH supervision and provide adequate protective equipment to reduce workplace accidents.